2014
DOI: 10.1080/10934529.2015.964602
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in wastewater: Occurrence and fate ofEnterobacteriaceaeproducers of Class A and Class C β-lactamases

Abstract: Antibiotics have been intensively used over the last decades in human and animal therapy and livestock, resulting in serious environmental and public health problems, namely due to the antibiotic residues concentration in wastewaters and to the development of antibiotic-resistant bacteria. This study aimed to access the contribution of some anthropological activities, namely urban household, hospital and a wastewater treatment plant, to the spread of antibiotic resistances in the treated wastewater released in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 55 publications
5
51
2
8
Order By: Relevance
“…However, little is known about the dissemination of this β-lactamase in an aqueous environment. Amador et al (Amador et al 2015) found bla EBC gene, including bla ACT , the most prevalent gene of the AmpC βlactamase type (38.9%). There was also a report on bla gene that was found in Enterobacter asburiae isolated from a water distribution network (Manageiro et al 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, little is known about the dissemination of this β-lactamase in an aqueous environment. Amador et al (Amador et al 2015) found bla EBC gene, including bla ACT , the most prevalent gene of the AmpC βlactamase type (38.9%). There was also a report on bla gene that was found in Enterobacter asburiae isolated from a water distribution network (Manageiro et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The number continues to grow. B-lactamase resistance genes belonging to the AmpC, ESBL, KPC, and NDM groups have been found in bacteria identified in wastewater (Zhang et al 2009;Picão et al 2013;Khan and Parvez 2014;Amador et al 2015;Varela et al 2016;Piotrowska et al 2017). However, our understanding of the diversity of types and variants is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Positive control strains were used in each set of PCRs, as described in previous studies [24,25]. For DNA Sanger sequencing (Macrogen, Amsterdam, The Netherlands), PCR products were purified using the GRS PCR & Gel Band Purification Kit (Grisp, Porto, Portugal).…”
Section: Characterization Of Resistance Genesmentioning
confidence: 99%
“…In den letzten Jahren haben sich wissenschaftliche Publikationen zum Vorkommen von antibiotikaresistenten Erregern einschließlich von Reserve-Antibiotika wie Carbapenemen und Colistin in Abwässern gehäuft [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Abwasserassoziierte Infektionsrisikenunclassified